2012
DOI: 10.3121/cmr.2012.1047
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automatic Diabetes Case Detection and ABCS Protocol Compliance Assessment

Abstract: Objective: According to the American Diabetes Association, the implementation of the standards of care for diabetes has been suboptimal in most clinical settings. Diabetes is a disease that had a total estimated cost of $174 billion in 2007 for an estimated diabetes-affected population of 17.5 million in the United States. With the advent of electronic medical records (EMR), tools to analyze data residing in the EMR for healthcare surveillance can help reduce the burdens experienced today. This study was prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This is particularly surprising because patients with diabetes can be identified with a reasonable degree of accuracy using structured data, such as diagnoses, medications and laboratory test results. 47,56 Furthermore, most studies in this area showed a similarly high level of accuracy, with almost all F 1 scores above 0.9. It is therefore likely that return on further investment in this particular area will be low and researchers' efforts would be more productively redirected elsewhere.…”
Section: Discussionmentioning
confidence: 92%
“…This is particularly surprising because patients with diabetes can be identified with a reasonable degree of accuracy using structured data, such as diagnoses, medications and laboratory test results. 47,56 Furthermore, most studies in this area showed a similarly high level of accuracy, with almost all F 1 scores above 0.9. It is therefore likely that return on further investment in this particular area will be low and researchers' efforts would be more productively redirected elsewhere.…”
Section: Discussionmentioning
confidence: 92%
“…The field continues to develop and some healthcare systems are partnering with industry to build CDSSs [78]. Recent work includes an NLP approach to assess adherence to treatment protocols and guidelines [79,80], automated medication dosing reminders in the operating room [81], screening for disease [82,83], prediction of hospital readmission [84,85], creation of a life-expectancy index for hospitalized elderly patients [86], determination of early indicators of patient deterioration [87], and guided urinary tract infection treatment [88]. Clinical decision support is not fully automated and issues such as human error in algorithm design can lead to underperformance [89].…”
Section: Clinical Decision Supportmentioning
confidence: 99%
“…In recent decades, text-mining methods have been used to analyse medical literature and professional documents (e.g. electronic medical records (EMR)) in order to detect risk factors of certain diseases from EMR [14] and the co-occurrence patterns of psychiatric and somatic diseases from medical literature [15]. Whereas, the associations were usually built on certain diseases and biological objects, such as genes, proteins and drugs [16,17].…”
Section: Related Workmentioning
confidence: 99%
“…Common approaches in this line of studies are usually based on terms co-occurrence [16,17], ontology-based concept association [15] and machine learning methods, such as classification [14]. Because the terms in professional medical documents are more standard than those in consumer-level medical text, medical thesaurus or ontologies are popularly used.…”
Section: Related Workmentioning
confidence: 99%